Perfil dos cirurgiões-dentistas e sua influência sobre o desempenho das Equipes de Saúde Bucal atuantes no Sistema Único de Saúde brasileiro - Suellen da Rocha Mendes (2019)
This study aimed to evaluate the influence of dentists' profile and work management in the performance of primary care dental teams of the Brazilian National Health System. Cross-sectional analysis of secondary data from the ‘National Programme for Improving the Access and Quality of Primary Care’ (PMAQ-AB), that evaluated 18,114 Brazilian dental teams between 2013 and 2014. Data were obtained from the external evaluation phase of the PMAQ-AB, which comprised the interview with the dentist regarding the dental team’s work process and verification of documents in the primary health care units. The questionnaire was developed through a partnership between the Ministry of Health and six teaching and research institutions and was applied by trained professionals. The dependent variable, ‘performance of dental teams’, was a score of dental teams obtained from the Item Response Theory, estimated though the psychometric analysis of 20 dental procedures executed in the PHC. Independent variables included complementary training, employment relationship and career plan of dentists and data referring to the management and organization of oral health services. Linear Regressions were performed to estimate the raw and adjusted Beta values, as well as their confidence intervals (CI 95%); in the adjusted model, variables with p≤0.05 were considered statistically significant. The results showed that the procedures with the highest difficulty levels (and less frequently performed) were those related to the provision of dental prostheses and oral cancer monitoring; the most discriminating procedures were restoration and extraction of primary teeth. The dental teams' performance ranged from -3.66 to +1.87 (mean -0.06; SD 0.82). The variables 'graduate studies', 'continuing education activities ', 'monitoring oral health indicators' and 'flexible dental appointment list (scheduled and walk in patients)' influenced the dental teams' performance in all Brazilian Geographical Regions. Variations in the execution of PHC dental procedures, dental teams' performance scores, and the variables that influenced such performances could be observed among the five Brazilian Geographical Regions. The findings suggest that the complementary training of the dentist, including continuing education training and graduate studies, the evaluation of oral health indicators of the enrolled population and the offer of a flexible appointment list, ensuring care to scheduled and walk in patients, had a positive impact in the performance of Brazilian dental teams.